A Spatial Approach: The Impact of Information and Communication Technology (ICT) Development on Reducing Educational Inequality in Papua, 2024 - Bayu Aji Bachtiar; Miftahus Sa'aadah; Udin Erawanto (Universitas Islam Balitar, 2026)
Education is a national development priority that is a strategic element in promoting the adoption of modern technology and sustainable growth, as reflected in National Long-Term Development Plan (RPJPN) 2025–2045 and the fourth Sustainable Development Goal (SDG). However, educational inequality in Papua and West Papua remains a serious challenge in terms of equitable access to quality education. This study aims to evaluate the impact of digital development on educational inequality in these two provinces. Secondary data from the Central Statistics Agency (BPS-Statistics) and the Directorate General of Fiscal Balance (DJPK) were analyzed using the Spatial Error Model (SEM) to examine the influence of Information and Communication Technology (ICT) on the Education Gini Coefficient (EGC). The results show that variables such as internet access for people aged 7-18 years, the Community Literacy Development Index (IPLM), Mean Years of School (MYS), and regional education budgets play a significant role in reducing educational inequality. These findings confirm that digital development plays a strategic role in creating an inclusive and equitable education system. This research is expected to serve as a basis for formulating adaptive technology-based education policies to overcome educational inequality in Papua Island.